Development, implementation, and evaluation of Teach Back curriculum for community health workers - Holcomb, Jennifer; Ferguson, Gayla M.; Thornton, Logan; Highfield, Linda (Frontiers in Medicine, 2022)
Teach Back is a commonly used communication method to improve patient understanding and retention of health information. The method has been shown to be effective in improving patient and healthcare system outcomes, including patient health literacy and hospital readmissions. Community Health Workers are frontline healthcare workers who can help address patient health and social needs associated with hospital readmissions. However, a gap exists in Teach Back curricula and training methods reflecting the scope of work for Community Health Workers. The objective of this training was to provide Community Health Workers with didactic information and skill building practice curriculum focused on the integration of Teach Back into clinical patient interactions, care coordination, and follow up support. A multidisciplinary team of academic and clinical partners at a large academic health university developed, implemented, and evaluated a three-week pilot Teach Back training with Community Health Workers through a quality improvement approach. The Community Health Workers reported overall satisfaction with the training and instructors. The academic clinical partnership allowed the training to be tailored to the daily clinical workflow as reflected in the Community Health Workers agreement that the training was relevant and practical. With the repeated exposure to Teach Back each week, the Community Health Workers also reported an increase in confidence and conviction in using Teach Back. Additional implementation and evaluation of the training curriculum for Community Health Workers is needed to gain further insights into Teach Back and training best practices and translation into practice.